Parent Perspectives on Family-Centered Care in Speech and Language Therapy Across Different Settings - Carpenter, Leah M. (My University, 2018)
The purpose of this study was to examine the differences in family-centered care (FCC) among speech and language pediatric therapy settings, including a university clinic setting. The logistics of speech and language therapy settings can help or hinder parent involvement and parent-therapist relationships, two key elements in FCC. High levels of parent involvement and collaborative parent- therapist relationships can produce the following benefits: increased parent satisfaction with therapy, decreased parent stress, and increased progress for the child. Six participants were recruited from the University of Wisconsin -Eau Claire Center for Communication Disorders (CCD). Participants' children received services at the CCD and at least one other speech and language therapy setting. Each participant engaged in one face-to-face interview, which was transcribed and analyzed using an open and axial qualitative coding method. The primary investigator (PI) and a research assistant (RA) collaborated to analyze and code the interviews to reach conclusions based on the presenting data. Results indicated that parents experienced various levels of involvement and collaboration with SLPs in the different settings. However, the logistics of the different settings may not be the primary influence; rather, it appeared that the SLPs and parents themselves were the more effective factors of collaborative relationships and levels of parent involvement. It was also discovered that parent perspectives of the university clinic differed from that of the other settings. Specifically, student clinicians were viewed more positively than practicing SLPs and the university clinic was repo1ied to be more effective, possibly due to the integration of research. These results demonstrate the need for SLPs working with children to create a positive relationship with parents to facilitate involvement and to integrate research into practice to further benefit the child.
Keywords: Children with disabilities--Education--United States--Language arts; Speech therapy for children